On the Impact of Information Flows on The Modern Formation of Competition and Foreign Economic Policy - Elena Vyacheslavovna ZENKINA1; Valery Maksimovich TUMIN2; Petr Aleksandrovich KOSTROMIN2 (Communications of International Proceedings, 2020)
The article considers the role of information technologies in the international economy and international relations’ evolution. The article describes the place of the information space in the multinational companies and developed countries’ global competitiveness formation. Information is presented as an important resource that affects the financial, industrial, innovation and investment spheres, and provides the companies and entire states’ advantages in the global economy. The Internet’s role in spreading planetary connections between people and infrastructure objects is analyzed. The world economy’s transition to a new development stage is presented as a transition to the information and digital economy. The key Internet technologies’ development stages are listed and the Internet state regulation problems are analyzed using examples of the Russian law "On information, information technologies and information protection", as well as the Chinese "Golden shield". The existing restrictions’ key circumvention technologies with the use of Internet tunnels are characterized. This topic is particularly relevant in the context of numerous countries’ accusations interfering in each other's internal affairs, including in the election process and influencing public opinion. Conclusions are made about the information and image confrontation’s role in solving the developed countries’ foreign policy problems.
Keywords: Global Challenges; International Economic Relations; Foreign Economic Policy.